Strategi Pengembangan dan Pengelolaan UMKM di Desa Mekarsari Tambun Selatan Bekasi - Purnamasari, Pupung; Syafitri Caniago, Laila; Alifya Putri, Tyara; Ismawanti, Windy; Putri Desyaksita, Zahra (Green Publisher Indonesia, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play an important role in the Indonesian economy, but many MSMEs face challenges in terms of marketing, management, and the use of digital technology. This research aims to identify digital-based MSME development and management strategies in Mekarsari Village, South Tambun, which can increase business competitiveness and sustainability. This research fills the gap in previous studies that focused more on the marketing aspect, by comprehensively examining the application of digitalization in the development of MSMEs. The method used is qualitative descriptive with a community service approach, which consists of stages of preparation, implementation, and evaluation. Data collection is carried out through field observations, interviews, and documentation studies. The results of the study show that the use of digital strategies such as attractive packaging design, consistent branding, website creation for marketing, and training in the preparation of financial statements has a positive impact on increasing sales and business management. In conclusion, the implementation of digitalization-based strategies is effective in increasing the competitiveness of MSMEs, and it is important to continue to provide assistance and training so that MSMEs in Mekarsari Village can adapt and develop in an increasingly competitive market.